ESTRATEGIAS BASADAS EN PROYECTOS Y SU IMPACTO EN EL APRENDIZAJE SIGNIFICATIVO DE 7MO EGB DE LA ESCUELA AURORA ESTRADA Y AYALA DE RAMÍREZ PÉREZ DE BABAHOYO PERIODO 2024.2025 - GUAPULEMA MARTINEZ DORIS MARIA (2024)
The objective of this degree work was to determine the impact of project-based strategies on meaningful learning since, currently, those techniques, strategies and ways for learners to promote meaningful activities must prevail, which is why this study It lies in the fact that the teacher must adequately teach these techniques, it is worth highlighting that a student must be constantly motivated to create interest in learning. This study was carried out based on a non-experimental investigation, estimating that from the given observation it was possible to verify that students do need a better implementation of activities, it prevails that project-based strategies establish a great impact on their cognitive development and therefore and therefore in their learning, so students consider that they learn on a large scale through problem solving, collaborative work, thus, the fulfillment of the hypothesis raised in this study is considered. Subsequently, the importance of project-based strategies is emphasized since it is essential to apply them, regardless of the area of knowledge, given that students in their training process learn in a holistic and comprehensive manner, in addition to that, many skills that the student learns are emphasized. possess and are not fluid or exposed within the classroom. Finally, it is highlighted that project-based strategies promote significant learning from a holistic and comprehensive perspective, as students create their own knowledge, which is why, currently, the teacher must be informed on a large scale about a wide variety of strategies that can be adapted to form students with significant and lasting knowledge for life.